Stakeholders Management Strategy Model as an Effort to Develop Partnerships - Ima Rahmawati Sushanti; Eko Budi Santoso (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2020)
To achieve a sustainable urban economic life, optimal support from the economic potential in urban areas is needed, especially the presence and support of stakeholders. The Industry, Cooperatives, Small and Medium Enterprises Office of Mataram City in West Nusa Tenggara Province, Indonesia is the main actor of the most dominant influential government agencies in the pearl gold and silver industrial cluster network which is one of the household-based business settlement areas that are still not optimal in its achievements, as a selected case study. This study was conducted to determine the achievement of agencies in the development of the pearl gold and silver industry cluster and determine the appropriate stakeholder management strategy model based on their interests and influence. The method used is descriptive qualitative and case studies using analysis of the level of influence and interest. The results of study show that the Industry, Cooperatives, Small and Medium Enterprises Office needs to intensively collaborate with the most influential and high-interest stakeholders to develop the industry cluster, namely stakeholders who are key stakeholders and context setters, namely Trading Office of Mataram City, Trading and Industry Office of West Nusa Tenggara Province, Tourism Office of Mataram City, Development Planning Agency at Sub-National Level of Mataram City, Ministry of Industry and Trading, National Development Planning Agency, the private sector, and financial institutions. Stakeholder management strategy model uses the Penta helix partnership model, which involves (1) the community, (2) the government, (3) private and financial institutions, (4) academics and associations also (5) media.